2023
DOI: 10.7554/elife.86453
|View full text |Cite
|
Sign up to set email alerts
|

Resting-state fMRI signals contain spectral signatures of local hemodynamic response timing

Abstract: Functional magnetic resonance imaging (fMRI) has proven to be a powerful tool for noninvasively measuring human brain activity; yet, thus far, fMRI has been relatively limited in its temporal resolution. A key challenge is understanding the relationship between neural activity and the blood-oxygenation-level-dependent (BOLD) signal obtained from fMRI, generally modeled by the hemodynamic response function (HRF). The timing of the HRF varies across the brain and individuals, confounding our ability to make infe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 108 publications
(193 reference statements)
3
6
0
Order By: Relevance
“…This suggests that either (a) there exists a common driver, such as the BOLD contrast itself, that impacts the two measures, but RSF and CVR are differently impacted over time, or (b) the impact of a common driving property is smaller than originally thought, or should be reconsidered altogether. This interpretation is in line with recent evidence of a stronger link between RSF and haemodynamic responses, specifically neurovascular coupling, than to CVR measured through a BH task (Bailes et al, 2023): while both RSF and CVR might describe a component related to neurovascular coupling, they are not necessarily linked to the same component. Hence, interpreting our results based on our unique dense sampling data, we join the point of view of Lipp et al (2015) and De Vis et al (2018) and express caution in adopting RSF measures interchangeably with CVR.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This suggests that either (a) there exists a common driver, such as the BOLD contrast itself, that impacts the two measures, but RSF and CVR are differently impacted over time, or (b) the impact of a common driving property is smaller than originally thought, or should be reconsidered altogether. This interpretation is in line with recent evidence of a stronger link between RSF and haemodynamic responses, specifically neurovascular coupling, than to CVR measured through a BH task (Bailes et al, 2023): while both RSF and CVR might describe a component related to neurovascular coupling, they are not necessarily linked to the same component. Hence, interpreting our results based on our unique dense sampling data, we join the point of view of Lipp et al (2015) and De Vis et al (2018) and express caution in adopting RSF measures interchangeably with CVR.…”
Section: Discussionsupporting
confidence: 90%
“…Fesharaki et al (2021) suggest that lower agreement between RSF measures and BH-induced CVR might be attributed to a lack of optimal thresholding of the corresponding maps. More recently, Huck et al (2023) showed that ALFF has a bias to the properties of venous vasculature, which might confirm the hypothesis that these RSF metrics are biased by resting cerebral blood volume (De Vis et al, 2018), although Bailes, Gomez, Setzer and Lewis (2023) attributes such bias more to the neurovascular coupling than to the CVR mechanism, since the latter does not include the same metabolic factors driving the former (D’Esposito, Deouell & Gazzaley, 2003; Iadecola, 2017; Pinto et al, 2021).…”
Section: Introductionmentioning
confidence: 73%
“…Since functional connectivity estimates are delay-sensitive, it could be that the exact boundaries at which networks segregate are influenced by differences in their hemodynamic response properties even if the underlying neuronal activity were synchronous. Although prior studies have not specifically tested this effect, their results often display a spatial pattern that resembles our observed delays (Amemiya et al, 2020;Bailes et al, 2023;Lewis et al, 2016, fig. 7).…”
Section: Anatomical Features Associated With Single-voxel Responsessupporting
confidence: 60%
“…A challenge for identifying precise timing information in fMRI is that the temporal properties of hemodynamic responses are highly heterogeneous across the brain (Bailes et al, 2023; Handwerker et al, 2004; Pfeuffer et al, 2003) and across experimental contexts (Chen et al, 2021; Friston et al, 1998; Handwerker et al, 2012). BOLD responses are influenced by the vascular architecture of the cortex: they are weaker but have an earlier onset in the parenchyma, and stronger in the large draining veins that collect large volumes of deoxygenated blood from multiple capillary beds (Turner, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation